Пользовательского поиска

X2, Y2, Z2 :

 

Qx2 = Jx2×wx2 - Jxy2×wy2 - Jxz2×wz2

Qy2 = Jy2×wy2 - Jyx2×wx2 - Jyz2×wz2 (3)

Qz2 = Jz2×wz2 - Jzx2×wx2 - Jzy2×wy2

 

-, - .1, :

 

) :

 

wx1 = wx0×cos(a) - wz0×sin(a)

wy1 = wy0 + a' (4*)

wz1 = wx0×sin(a) + wz0×cos(a)

wx1' = wx0'×cos(a) - wz0'×sin(a)

wy1' = wy0' + a'' (4*')

wz1' = wx0'×sin(a) + wz0'×cos(a)

 

) :

 

wx2 = wx1×cos(b) + wy1×sin(b)

wy2 = wy1×cos(b) - wx1×sin(b) (5*)

wz2 = wz1 + b'

wx2' = wx1'×cos(b) + wy1'×sin(b)

wy2' = wy1'×cos(b) - wx1'×sin(b) (5*')

wz2' = wz1' + b''

 

2- (5*) , :

wy1=wx1×tg(b)+wy2/cos(b)

 

2- (5*') , :

wy1'=wx1'×tg(b)+wy2'/cos(b)

 

, , wy2, wz2, wy2', wz2' , .. , :

wx1 = wx0×cos(a) - wz0×sin(a)

wy1 = wx1×tg(b)+wy2/cos(b) (4)

wz1 = wx0×sin(a) + wz0×cos(a)

wx1' = wx0'×cos(a) - wz0'×sin(a)

 

 Rambler's Top100